(σ, f)-Asymptotically Lacunary Equivalent Sequences. (3rd December 2014) - Bilgin, Tunay
Abstract : We introduce the strong( σ, f ) -asymptotically equivalent and strong( σ, f ) -asymptotically lacunary equivalent sequences which are some combinations of the definitions for asymptotically equivalent, statistical limit, modulus function, σ -convergence, and lacunary sequences. Then we use these definitions to prove strong( σ, f ) -asymptotically equivalent and strong( σ, f ) -asymptotically lacunary equivalent analogues of Connor's results in Connor, 1988, Fridy and Orhan's results in Fridy and Orhan, 1993, and Das and Patel's results in Das and Patel, 1989.